Teacher Technological Leadership for Society 5.0 - Samsudin, Norhanida; Mohd Noor, Mohd Asri (International Business Education Journal, 2025)
Education plays an important role in building a society aspired to by the nation. Society 5.0 is soon to be a reality instigated by the industrial revolution affecting changes in daily life. These changes affected not only working processes but also the fields of work. Hence, a nation that seeks to move forward with the times must surely have human resources that are able to fulfill the economic needs, as well as people who are willing to live in harmony regardless of the changes that occur, especially in technological advancements. Thus, education is pivotal in supporting individual needs with life skills for now and the future. Teacher technological leadership is an asset to the school. Teachers in all fields of expertise, including business education, mathematics, science, language and many more, should not only be capable of leadership, either formally or informally, but also lead in technological integration in teaching and learning. Through teacher technological leadership, teachers can support learners’ technological development ethically whilst prioritizing humanity in preparing learners to be valuable members of Society 5.0. Therefore, this article will discuss the concept of Society 5.0, teacher technological leadership and its practice.